2016
DOI: 10.3847/0067-0049/225/2/24
|View full text |Cite
|
Sign up to set email alerts
|

NUGRID STELLAR DATA SET. I. STELLAR YIELDS FROM H TO BI FOR STARS WITH METALLICITIES Z = 0.02 and Z = 0.01

Abstract: We provide a set of stellar evolution and nucleosynthesis calculations that applies established physics assumptions simultaneously to low-and intermediate-mass and massive star models. Our goal is to provide an internally consistent and comprehensive nuclear production and yield database for applications in areas such as presolar grain studies. Our non-rotating models assume convective boundary mixing (CBM) where it has been adopted before. We include 8 (12) initial masses for Z = 0.01 (0.02). Models are follo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
218
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(255 citation statements)
references
References 279 publications
10
218
2
Order By: Relevance
“…In fact, a higher amount of 12 C in the intershell leads to a higher abundance of 13 C, and subsequently a higher number of free neutrons. Full s-process models including this effect have been developed by Pignatari et al (2016) and Battino et al (2016).…”
Section: Current Models For the Formation Of 13 C Pocketsmentioning
confidence: 99%
“…In fact, a higher amount of 12 C in the intershell leads to a higher abundance of 13 C, and subsequently a higher number of free neutrons. Full s-process models including this effect have been developed by Pignatari et al (2016) and Battino et al (2016).…”
Section: Current Models For the Formation Of 13 C Pocketsmentioning
confidence: 99%
“…Instead, one-zone simulations-although constituting a further simplification, allow studying the nucleosynthesis that may be possible in this event in isolation. The dynamic NuGrid network includes as required up to 5234 isotopes with associated rates from JINA Reaclib V1.1 (Cyburt et al 2010) and other additional sources (see Pignatari et al 2016). The general strategy is to approximate the nucleosynthesis through a series of three one-zone calculations which start with H burning followed by He burning and finally, we add in the last step a small amount of H to the partially completed He-burning nucleosynthesis calculation to estimate the nucleosynthesis due to H ingestion.…”
Section: Nucleosynthesis Calculationsmentioning
confidence: 99%
“…To be rigorous in our comparisons, we combine OMEGA with the Markov Chain Monte Carlo (MCMC) code described in ForemanMackey et al (2013) to derive the set of parameters for each model that best fits the observed stellar abundances in Sculptor. All numerical predictions and observational data shown in this work are normalized to the solar composition found in Grevesse & Noels (1993), which is the one adopted in NuGrid models (see Pignatari et al 2016).…”
mentioning
confidence: 99%
“…Our motivation is to bridge the fields of nuclear physics, stellar evolution, galaxy evolution, cosmological structure formation, and modern statistical methods. This framework consists of a chain of models that so far includes the NuGrid stellar evolution models which use the JINA ReacLib nuclear reaction network (Pignatari et al 2016;Ritter et al in prep. ), the SYGMA (Stellar Yields for Galactic Modeling Applications, Ritter et al in prep.)…”
mentioning
confidence: 99%